Typhoid fever with severe pancytopenia. - Sood, R. (BMJ Group, 1997)
A patient suffering from typhoid fever with severe pancytopenia is presented. Bone marrow examination revealed extensive haemophagocytosis which possibly contributed to the pancytopenia.